Kebijakan Inovatif Kepala Sekolah Efektif dalam Pengembangan Mutu SDM di MIN 1 Yogyakarta - Farah Alfian Ghofar Rahmat; Nazilatul Mifroh; Aan Fadia Annur (Islamic Elementary School Teacher Education Study Program, Faculty of Education and Teacher Training, K.H. Abdurrahman Wahid Pekalongan State Islamic University, Indonesia, 2021)
In the composition of the composition, drawing conclusions is a part especially in planning activities. This study aims to explain and examine in detail the principal's leadership in drawing conclusions made by the MIN 1 Yogyakarta headmaster in developing the quality of human resources and explaining the implementation of the initiative. This observation is a qualitative descriptive study with background setting in MIN 1 Yogyakarta. Data collection methods use observation, interviews and data collection